2020
DOI: 10.21315/mjms2020.27.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Suicidal Behaviours after Natural Disasters: A Systematic Review

Abstract: Natural disasters have multiple psychological effects including increased risk of suicide among victims. Reviews have shown that suicidal behaviours can be an aftermath of natural disasters. The present study attempted to identify the suicide-related risk factors after natural disasters. This study was a systematic review probing English language articles related to suicide and its risk factors after natural disasters and published between 1 January 1990 and 27 September 2018 in Google Scholar, PubMed, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 65 publications
1
33
1
1
Order By: Relevance
“…In this study, the objective trauma characteristics of the loss of family members and being buried were significant predictors of PTSD severity, and they explained a significant 21.9% of the variance. These findings were in accord with those of previous studies, which demonstrated that children with more severe exposure to the traumatic event had more PTSD symptoms ( 24 , 25 ). The loss of family members affects the emotional attachment system in children.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the objective trauma characteristics of the loss of family members and being buried were significant predictors of PTSD severity, and they explained a significant 21.9% of the variance. These findings were in accord with those of previous studies, which demonstrated that children with more severe exposure to the traumatic event had more PTSD symptoms ( 24 , 25 ). The loss of family members affects the emotional attachment system in children.…”
Section: Discussionsupporting
confidence: 92%
“…A second important limitation is that censoring might underestimate the effects of some psychiatric disorders on mortality. Recent reports identified specific psychiatric diseases or symptoms as important risk factors for suicide after natural disasters 33 . Moreover, it is also important to consider that old age is one of the risk factors for post-disaster suicide 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports identified specific psychiatric diseases or symptoms as important risk factors for suicide after natural disasters 33 . Moreover, it is also important to consider that old age is one of the risk factors for post-disaster suicide 33 . The target population in this study included patients who had achieved community transitions and might have become somewhat independent from medical practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Natural disasters have many psychological effects, including an increased risk of suicide among victims. Therefore, there is a need to provide psychosocial support to these people [35]. AI should have an emotional intelligence component to effectively reduce public anxiety and motivate people to take corrective or preventive actions.…”
Section: What Emotionally Intelligent Ai Could Do?mentioning
confidence: 99%